Critical incident exposure among custody and noncustody correctional workers: Prevalence and impact of violent exposure to work‐related trauma. Issue 6 (5th April 2022) - Jaegers, Lisa A.; El Ghaziri, Mazen; Katz, Ian M.; Ellison, Jared M.; Vaughn, Michael G.; Cherniack, Martin G.
Abstract: Background: Correctional workers are at high risk for exposure to trauma, both as direct violence and as threats to their safety and well‐being. The distress associated with these critical incidents (CIs) affects mental and physical health. Current tools are limited for detecting CIs in this workforce and are therefore insufficient for addressing correctional worker trauma. Methods: Community prison employees ( N  = 105) self‐reported CIs using the adapted Correctional Worker Critical Incident Survey (CWCIS). We examined: (1) prevalence of CIs and occurrences, (2) differences in exposures to CIs by custody and noncustody staff, and (3) differences in job satisfaction, posttraumatic stress (PTSD), lower back disease, and health behaviors, such as missed work and sleep. Results: CIs occurred among most staff (59%) and more often for custody staff as compared to noncustody staff. CIs most often experienced were c oworker injury, exposure to disease, and badly beaten adults (frequency 10−50). For the 1−9 frequency category, the most described events were: seeing someone dying, life threatened, and coworker injury . PTSD was identified in 44% of staff, and those who experienced CIs reported lower job satisfaction, greater feelings of PTSD, and more work absences than those not experiencing CIs ( p  < 0.05). Conclusions: CIs and PTSD are prevalent among custody and noncustody correctional workers; and job dissatisfaction, PTSD, and work absence are significantly worse for those who experienced CIs. The CWCIS detected CIs; future study is needed to inform trauma prevention, reduction, and rehabilitation interventions specific to correctional work.